(3GdePjY h af JbOje GdHQGeL ddQGOjh h GdJdjaRjhf (B/s - (3TdHj, cQe s ((3GdbGgQI (B:s (3ecJHI GdJQGK GdESdGej ,s, 1992)
(3jJfGhd aj gPG GdcJGH cd eG jJUd Yf GdPjY h af JbOje GdHQGeL aj GdEPGYI GdeSehYI h GdGPGYI GdeSehYI GdeQFjI Gj aj GdQGOjh h GdJjdjaRjhf s
(3HHdjhZQGajG (B: (3U(B.251-358s
Keywords: (3GdJdaRjhf s; (3GdQGOjhs; (3SeYj HUQjs; (3GdEPGYIs